Pengaruh Model Pembelajaran Make a Match Terhadap Kemampuan Pemecahan Masalah Matematika Siswa di SDN Keras 2 - Chofifah, Aprilia Eka; Raharja, Hawwin Fitra; Susilo, Claudya Zahrani (IJPSE Indonesian Journal of Primary Science Education, 2024)
The importance of problem-solving skills for students because help them think, grasp, apply what they know, and develop other mathematical skills. Therefore, in learning mathematics, problem-solving skills should be a top priority. This model is used as an active and enjoyable learning model, but still a consistent learning objective. The purpose of this study is to provide an understanding of how learning models make a match affect students' ability to solve problems. This research is a quantitative study with design one group retest-posttest. The sample population of this initiative consisted of 20 V-grade students. Data analysis results showed that the average pretest before treatment was 62 and the average posttest after treatment was 82.65. Overall, the students' problem-solving skills improved on pretest and posttest issue, with an average presentation of 46%. Therefore, student's problem solving ability improved after application the "make a match" learning model.